Faktor Yang Berhubungan Dengan Kepatuhan Tenaga Kesehatan Menggunakan Alat Pelindung Diri (APD) Di Era Pendemik Covid 19 Pada Puskesmas Makkasau Makassar Tahun 2020 - Lany Hakim; Muh. Khidri Alwi; Alfina Baharuddin (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Introduction: The Covid-19 case in Indonesia itself, the government has issued a disaster emergency status starting on February 29, 2020, regarding this virus pandemic. Personal protective equipment (PPE) is used to protect yourself or the body against the dangers of work accidents and the risk of contracting the virus, especially related to biological hazards, health workers are at the forefront of breaking the chain of transmission of Covid 19 because they are located in each sub-district and have a regional concept so that the use of PPE is one of the main procedures in the health service process. where factors related to the compliance of health workers using PPE are knowledge, years of service, formal education, supervision, and workload. The purpose: of this study was to determine the relationship with the compliance of health workers using PPE in the COVID-19 pandemic era at the Makassar Makassar Health Center. This research method: is a quantitative study using the Analytical Survey with a cross-sectional study approach. Data analysis using logistic regression test. The sampling technique in this study was total sampling with a sample size of 42 health workers. The Results: of statistical test research using the chi-square test found that of the three variables, namely work period (p = 0.037), supervision (p = 0.002), and workload (p = 0.014) had a significant relationship with adherence to using PPE. Meanwhile, formal education (p = 0.702) and knowledge of 100%, did not have a significant relationship with compliance with using PPE. The conclusion: of this study shows that there is a significant relationship between tenure, supervision and workload with compliance with using PPE at Makkasau Public Health Center in Makassar. It is recommended that the health center should increase supervision in the use of PPE and pay attention to the workload of health workers